2020
DOI: 10.1002/prot.25990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of left‐handed beta helix‐domains, and identification and functional annotation of proteins containing such domains

Abstract: Only about 0.3% of the entries in UniProt database have manually curated annotation. Annotation at the molecular level often relies on low‐throughput one‐protein‐at‐a‐time approach. Computational methods bridge this gap by assigning function based on sequence and/or fold similarity. Left‐handed beta helix (LbH) consists of three repeating six‐stranded beta‐strands forming an 18‐mer turn of the helix. Analysis of LbH‐domains showed that variations are found in the number of residues in a beta‐strand (5‐7, 6 bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…They were labelled according to their solvent exposition: buried (b), exposed (e) and partially exposed (p). 36 They are composed of six residues, hence termed hexad, four for the β-strand (B1, B2, B3, B4), and 2 for the turn (T1, T2). 29 Of note, in positions B1 and B3, the residues are oriented inwards, hence forming the hydrophobic core, whereas the others are oriented outwards of the helix (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were labelled according to their solvent exposition: buried (b), exposed (e) and partially exposed (p). 36 They are composed of six residues, hence termed hexad, four for the β-strand (B1, B2, B3, B4), and 2 for the turn (T1, T2). 29 Of note, in positions B1 and B3, the residues are oriented inwards, hence forming the hydrophobic core, whereas the others are oriented outwards of the helix (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…As such, they belong to the so-called "capping motifs" at the extremities of the helix that are the structural elements, belonging to the β-helix or not, responsible for the solubility of the protein. 7,[33][34][35][36] It has indeed been shown that removing capping motifs of β-solenoids, including left-handed β-helix, allows their self-assembly into fibers. 22,23,27 While these aspects were considered by Balaram and coworkers first, and later by Prabha and Balaji, they did not provide a specific analysis of the sequence of these N-terminal and C-terminal rungs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation